Upaya Meningkatkatan Hasil Belajar Peserta Didik Kelas II SDN 2 Batu Buil dalam Pembelajaran Pak Melalui Model Pembelajaran Problem Based Learning (PBL) - Ernawati Ernawati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve learning outcomes for Catholic Religious Education and Character through the Problem Based Learning (PBL) method in class 2 of SDN 2 BatuBuil in the 2024/2025 academic year. The type of research is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation and reflection. The material discussed is